The Human Microbiome: Composition, Function, and Impact on Health - Haripriya G; Alen Geo Wilson; Binsu Binu; Asha Spandana K M (Pharmaceutical Research - Recent Advances and Trends Vol. 2, 2024)
Microbiome is the collective term for all the microorganisms, both symbiotic and pathogenic. Microbes in the microbiome may be helpful or harmful, depending on their function. They are typically symbiotic and beneficial to both the human body and the microbiota. In a healthy body, pathogenic and symbiotic bacteria coexist without conflict. A dysbiosis develops when that balance is disrupted, which can be caused by viral infections, particular diets, or extended antibiotic usage. As a result, the body may be more vulnerable to disease. The human body’s various functions, including metabolism and immune system activation, depend on the synergic microbiome, which is crucial for human health. There is growing evidence that some alterations in the microbiome contribute to the emergence of certain illnesses, such as infections by pathogens, diabetes, liver ailments, and cancers. Consequently, altering the microbiome is emerging as a cutting-edge and successful way to treat many illnesses. By enabling researchers to generate strains with distinct and intricate activities, synthetic biology opens up the possibility of using created microbes for therapeutic purposes. This review aims to provide an overview of current research on the involvement of the microbiome in specific diseases and the underlying mechanisms, as well as the application of modified bacteria in disease diagnosis and prevention. The gut microbiota, or the billions of microorganisms that reside there, is crucial to human health and disease. Even though a lot of work has been done to investigate its diversity, an evolutionary viewpoint is necessary to fully comprehend our microbiomes. In this review, we examine human population microbiomes and compare them with bacteria from close and distant animal relatives of humans. We talk about possible ways to create host-specific microbiome configurations and what happens when those configurations are disturbed. We conclude by suggesting that a more comprehensive knowledge of the mechanisms underpinning human-microbiome interactions can be gained from this larger evolutionary perspective.